2021
DOI: 10.1108/ijebr-05-2020-0321
|View full text |Cite
|
Sign up to set email alerts
|

Economic regulation, opportunity-driven entrepreneurship and gender gap: emerging versus high-income economies

Abstract: PurposeInstitutional environment plays a crucial role in determining the nature of entrepreneurship that prevails in an economy. In this paper, the authors address how business, labour and credit regulations contribute differently to both the overall prevalence of opportunity-driven entrepreneurship (ODE) and its gender gap in high-income and emerging economies.Design/methodology/approachOn the basis of an unbalanced panel of 41 countries over the period 2005–2016, the authors estimate system generalised metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Empirical research has not provided conclusive results on the effect of economic freedom on entrepreneurial activities. Scholars have analysed the role of formal institutions in different entrepreneurial types as opportunity-driven (Angulo-Guerrero et al, 2017;Bárcena-Martín et al, 2021;Díaz-Casero et al, 2012;Raza et al, 2019), necessity-driven (Goel & Saunoris, 2020;Kuckertz et al, 2016;McMullen et al, 2008), selfemployed (Goetz & Rupasingha, 2014;Nyström, 2008;Özkul, 2020), and the establishment of formal business (Ajide, 2021;Barnatchez & Lester, 2017;Bennett, 2021a;Hall et al, 2016;Kosi & Bojnec, 2013;Raza et al, 2019;Sweidan, 2021). Table 1 summarizes the main empirical and theoretical findings on this topic.…”
Section: 2economic Freedom and Entrepreneurshipmentioning
confidence: 99%
“…Empirical research has not provided conclusive results on the effect of economic freedom on entrepreneurial activities. Scholars have analysed the role of formal institutions in different entrepreneurial types as opportunity-driven (Angulo-Guerrero et al, 2017;Bárcena-Martín et al, 2021;Díaz-Casero et al, 2012;Raza et al, 2019), necessity-driven (Goel & Saunoris, 2020;Kuckertz et al, 2016;McMullen et al, 2008), selfemployed (Goetz & Rupasingha, 2014;Nyström, 2008;Özkul, 2020), and the establishment of formal business (Ajide, 2021;Barnatchez & Lester, 2017;Bennett, 2021a;Hall et al, 2016;Kosi & Bojnec, 2013;Raza et al, 2019;Sweidan, 2021). Table 1 summarizes the main empirical and theoretical findings on this topic.…”
Section: 2economic Freedom and Entrepreneurshipmentioning
confidence: 99%
“…For Aparicio et al [29], opportunity entrepreneurship is identified as one of those mechanisms that impacts economic growth; furthermore, they indicate that informal institutions have a greater impact on opportunity entrepreneurship than formal institutions. González et al [30] indicates that the discovery of opportunities and the creation of opportunities are mutually exclusive constructions, while credit market regulation stands out as a key element in promoting opportunity-based entrepreneurship in both high-income and emerging countriesBarcena-Martin et al [31]. For Dey [32] entrepreneurship in crisis conditions is not so much a matter of necessity; it is an opportunity to redefine the scope of economic practice with its own rules.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors verify that to increase opportunity driven entrepreneurship, elements relating to social equality, education and sustainability are also relevant together with the presence of a dynamic and favorable economic context. [9] analyze the role of the entrepreneurial, labor, credit, and gender gap system in determining the institutional context favorable to opportunity driven entrepreneurship. The authors analyzed data from 41 countries over the period 2005-2016.…”
Section: Literature Reviewmentioning
confidence: 99%